PT Pertamina (Persero)'s Perspective on the Development of Efforts to Empower SMEs in the Small Medium Enterprise Partnership Program (SMEPP) in the Jakarta Region - Maysa Syifa Aljauza; Sari Viciawati Machdum (Cita Konsultindo Research Center, 2024)
Companies must fulfill their Corporate Social Responsibility (CSR) in conducting business. One of the goals of CSR is to enhance the economy through empowering of MSMEs (Micro, Small, and Medium Enterprises). By empowering MSMEs, economic growth will be further enhanced. Some studies discussing